Beyond Implicit Bias: Embodied Cognition, Mindfulness, and Critical Reflective Practice in Social Work. Issue 2 (3rd April 2021) - Wong, Yuk-Lin Renita; Vinsky, Jana
ABSTRACT: Implicit bias studies in psychology and cognitive science focus primarily on the individual self, and more recently on the brain. In this article, we argue that the embodied cognition paradigm, which encompasses both the functional body and the environment, can provide more relevant insights for social work. Implicit bias is not just in the brain. It is in the dynamic systems process of a living body that constitutes, and is constituted by, the social, cultural and historical conditions. We explore the potential of mindfulness combined with critical reflective practice in catching and processing the visceral moment of bias and in interrupting its effect. We underline the importance of including interventions that target the environment—the cultural and social context—which constitutes the other aspect of embodied cognition. We argue for the development of integrated and multi-faceted intervention strategies to address implicit bias that include professional training in embodied self-awareness as well as organisational and institutional changes. IMPLICATIONS: The embodied cognition paradigm that integrates the body and the environment offers a wider lens to address implicit bias than the current dominant psychological and biological focused approach. Teaching body awareness combined with critical reflective practice can enhance anti-oppressive and critical social work practice. Intervention strategies to interrupt the impact of implicit bias must be multi-faceted to include the whole dynamic body system and the organisational and cultural contexts.